Automation of train cab front cleaning with a robot manipulator - Moura, João; McColl, William; Taykaldiranian, Gerard; Tomiyama, Tetsuo; Erden, Mustafa Suphi (IEEE, 2018)
In this letter we present a control and trajectory tracking approach for wiping the train cab front panels, using a velocity controlled robotic manipulator and a force/torque sensor attached to its end effector, without using any surface model or vision-based surface detection. The control strategy consists in a simultaneous position and force controller, adapted from the operational space formulation, that aligns the cleaning tool with the surface normal, maintaining a set-point normal force, while simultaneously moving along the surface. The trajectory tracking strategy consists in specifying and tracking a two dimensional path that, when projected onto the train surface, corresponds to the desired pattern of motion. We first validated our approach using the Baxter robot to wipe a highly curved surface with both a spiral and a raster scan motion patterns. Finally, we implemented the same approach in a scaled robot prototype, specifically designed by ourselves to wipe a 1/8 scaled version of a train cab front, using a raster scan pattern.
Keywords: Force; Tools; Cleaning; Robot sensing systems; Manipulators; Aerospace electronics; Kinematics; Industrial robots; Motion control; Force control